The Lece-Chalkidiki metallogenic zone: geotectonic setting and metallogenic features - Serafimovski, Todor (Geologija, 1999)
Several characteristics define the contours of this significant metallogenic zone developed owing to post collision tectonomagmatic processes along the contact between the Vardar zone and Serbo-Macedonian massif (SMM): regional and local fracture structures, surface manifestations of the Tertiary volcanogene-intrusive magmatism and polymetallic mineralization styles (Pb-Zn, Cu, Au, Sb, As). The most striking are the fractures of NNW - SSE strikes as well as ring-radial ones typical of the volcanic structures (Leče, Zletovo, Pontokerasia). The absolute age of the calc-alkaline volcanic complexes ranges from 37 to 16 m.y. The strontium ratios for these magmatic rocks indicate a contamination of magma by material from the continental crust (87Sr/86Sr 0.706318 - 0.706928). Ore deposits are grouped into several metallogenic districts and ore fields each characterized by specific styles of mineralization and a mineral/elemental association.